Ghosting Phenomenon in Interpersonal Communication of Bumble Application Users - Ramadini, Fadia; Radjagukguk, Djujur Luciana (International Peneliti Ekonomi, Sosial dan Teknologi, 2024)
Technological developments have made it easier for humans to build interpersonal relationships, one of which is using dating apps. One phenomenon that is often found in dating apps is the ghosting phenomenon. The ghosting phenomenon is an indirect termination of relationships that can hinder communication. However, many adult couples often fail or experience a breakup when they are at the approach stage. In general, someone experiencing the termination of a relationship or losing a partner can be a very traumatic and sad experience and can disrupt a person's mental health. This research aims to find out at what stage the ghosting phenomenon occurs in interpersonal communication on the dating app Bumble. This research uses a phenomenological research method with a qualitative approach, data collection techniques of in-depth interviews and observation. The theory used is the Social Penetration Theory which has four stages in a relationship, namely the orientation stage, affective exploratory exchange, affective exchange and stable exchange. The results of this research show that the ghosting phenomenon can occur at every stage of a relationship, during the introduction stage or when the relationship is already close to each other. This experience of ghosting behavior also creates communication barriers between people and leaves the victim feeling uncomfortable.